2016
DOI: 10.1021/acs.jpclett.6b01621
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence of Liquid–Liquid Phase Separation in Organic Aerosol

Abstract: Atmospheric aerosol particles influence climate through their direct and indirect effects. These impacts depend in part on the morphology of the particles, which is determined by their composition. The effect of pH on morphology was investigated using particles composed of 3-methylglutaric acid and ammonium sulfate by manipulating the starting pH of the bulk solution through the addition of aqueous sodium hydroxide. Efflorescence, deliquescence, phase separation, and mixing transitions were observed with optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 49 publications
2
106
1
Order By: Relevance
“…The change in correlation strength with increasing RH suggests that uptake is limited by the term Γ sol + Γ rxn ( and/or ) at low RH, but becomes limited by a different process, such as α as water availability increases (e.g., Bertram & Thornton, ; Thornton & Abbatt, ). The exact RH associated with this sensitivity change is thought to depend on the deliquescence point of each aerosol type and its propensity to form supersaturated liquids (e.g., Kane et al, ), which can be impacted by aerosol acidity and organics (e.g., Losey et al, ). In addition, several studies have observed the opposite, decreasing trend in γ (N 2 O 5 ) with RH on highly acidic sulfuric acid particles (Fried et al, ; Hallquist et al, ; Hu & Abbatt, ; Kane et al, ; Mozurkewich & Calvert, ), which supports an alternative, acid‐catalyzed mechanism discussed in section 4.2.5.…”
Section: Discussionmentioning
confidence: 99%
“…The change in correlation strength with increasing RH suggests that uptake is limited by the term Γ sol + Γ rxn ( and/or ) at low RH, but becomes limited by a different process, such as α as water availability increases (e.g., Bertram & Thornton, ; Thornton & Abbatt, ). The exact RH associated with this sensitivity change is thought to depend on the deliquescence point of each aerosol type and its propensity to form supersaturated liquids (e.g., Kane et al, ), which can be impacted by aerosol acidity and organics (e.g., Losey et al, ). In addition, several studies have observed the opposite, decreasing trend in γ (N 2 O 5 ) with RH on highly acidic sulfuric acid particles (Fried et al, ; Hallquist et al, ; Hu & Abbatt, ; Kane et al, ; Mozurkewich & Calvert, ), which supports an alternative, acid‐catalyzed mechanism discussed in section 4.2.5.…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of studies using electron microscopy and X‐ray spectroscopy methods to investigate aerosol particles have been published over the years, ranging from studies characterizing the constituents of specific types of aerosol, such as marine, mineral, dust, and biomass (Buseck & Pósfai, ; Li et al, ; Pósfai et al, , ) to those focused specifically on characterizing per‐particle composition and morphology (Deboudt et al, ; Pósfai et al, ), phase transitions (Wise et al, ), hygroscopic behavior (Okada, ; Semeniuk et al, ), phase separation (Ault et al, ; Freedman, ; Losey et al, ; O'Brien et al, ; You et al, ), and other important aerosol physicochemical properties that impact mixing state. However, only in the past few years have these methods begun to be used to quantify aerosol mixing state, the examples of which are discussed later in section .…”
Section: Measurement Techniques For Aerosol Mixing Statementioning
confidence: 99%
“…Few methods can directly measure the pH of aerosol (Rindelaub et al, 2016;Craig et al, 2018;Wei et al, 2018), so aerosol acidity is usually presented using indirect proxies such as ion balance (cationto-anion (Yao et al, 2006;Du et al, 2010;Zhou et al, 2017). However, these indirect methods can lead to substantial uncertainty in acidity assessment (Hennigan et al, 2015;Guo et al, 2016;Murphy et al, 2017). Calculation of pH through thermodynamic modelling such as E-AIM (Clegg et al, 1998) and ISORROPIA II (Fountoukis and Nenes, 2007), with the input of reliable chemical compositions of the aerosol and at least one semi-volatile gas and meteorological data, has been shown to be a more rigorous approach to calculate the pH of aerosol liquid water.…”
Section: Introductionmentioning
confidence: 99%
“…Calculation of pH through thermodynamic modelling such as E-AIM (Clegg et al, 1998) and ISORROPIA II (Fountoukis and Nenes, 2007), with the input of reliable chemical compositions of the aerosol and at least one semi-volatile gas and meteorological data, has been shown to be a more rigorous approach to calculate the pH of aerosol liquid water. Murphy et al (2017) and Song et al (2018) both showed that the constraint from phase partitioning of NH 3 /NH + 4 should be included in calculations using aerosol thermodynamic models to get reliable pH calculations, which indicates that NH 3 observation can greatly improve the reliability of the aerosol acidity assessment.…”
Section: Introductionmentioning
confidence: 99%